Assessment and interpretation of blood pressure variability in a clinical setting. (December 2013) - Parati, Gianfranco; Ochoa, Juan Eugenio; Lombardi, Carolina; Salvi, Paolo; Bilo, Grzegorz
Abstract Blood pressure (BP) is characterized by marked fluctuations occurring within the 24 h as a result of complex interactions between behavioral, environmental, humoral, and neural central or reflex influences. Significant BP variations also occur over more prolonged periods of time (i.e. between days, weeks, months, seasons and even years), not as a random phenomenon but as a result of several interacting factors yet not completely identified. Depending on the method and time interval considered for measurement, the clinical significance and prognostic implications of different types of BP variability (BPV) may substantially differ. Either in the short or in the long term, BPV has been associated with development, progression and severity of cardiac, vascular and renal organ damage and with an increased risk of cardiovascular events and mortality, independently adding to cardiovascular risk, over and above the contribution of elevated mean BP levels. The present paper provides a review on the main methods currently employed for assessment of BPV as well as on the mechanisms, clinical interpretation and prognostic significance of different types of BPV, addressing the question on whether BPV should be a target for antihypertensive treatment for the current prevention of cardiovascular disease.